2014
DOI: 10.1103/physrevb.89.195432
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear photoluminescence properties of trions in hole-doped single-walled carbon nanotubes

Abstract: We studied the excitation density dependence of photoluminescence (PL) spectra of excitons and trions (charged excitons) in hole-doped single-walled carbon nanotubes.We found that the PL intensity of trions exhibited a strong nonlinear saturation behavior as the excitation density increased, whereas that of excitons exhibited a weak sublinear behavior. The strong PL saturation of trions is attributed to depletion of doped holes that are captured by excitons in the formation processes. Moreover, the effective r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 34 publications
4
22
0
Order By: Relevance
“…30,31) The three-level system consists of free excitons (X), localized excitons (L), and ground (g) states, as shown in the inset in Fig. 4(b).…”
mentioning
confidence: 99%
“…30,31) The three-level system consists of free excitons (X), localized excitons (L), and ground (g) states, as shown in the inset in Fig. 4(b).…”
mentioning
confidence: 99%
“…2(b)], which may be caused by a reduction of E 22 absorption cross section or changes in Auger recombination rates. In addi- (8,6), (9,7), and (14,3) nanotubes, respectively. Data are taken at zero gate voltage (black broken lines) and under an application of gate voltages (red solid lines).…”
mentioning
confidence: 99%
“…1(b)]. These investigations complement studies of gate-dependent Raman [13,14,27,28,41] and photoluminescence [13,37] spectroscopy of air-suspended nanotubes, gate-dependent Rayleigh scattering spectroscopy of individual nanotubes on substrates [52], and chemically-carrier-doped nanotubes [38,44,[47][48][49]51,53,57,61,62] showing spectral features attributed to formation of charged excitons (trions) [38]. We present all the Rayleigh spectra corrected for the ω 3 scattering efficiency factor to reflect directly the optical susceptibility.…”
Section: Introductionmentioning
confidence: 59%
“…Hence, the energy separation of the exciton and trion peaks is expected to be much larger than the energy range of the observed shift and broadening of the exciton peaks. Moreover, it has been reported that the optical absorption feature from the creation of trions is much smaller (less than 1/10) than that of the exciton absorption feature even under conditions of relatively heavy doping using chemical treatments [38], presumably because of the small oscillator strength of trions [57]. In the case of Rayleigh scattering spectra, the peak intensity from the creation of trions (if present) is expected to be still smaller because Rayleigh scattering cross section is proportional to the square of the optical susceptibility.…”
Section: B Exciton Energy Shiftmentioning
confidence: 99%